A CROSS-ROAD TO QHAPAQ ÑAN BETWEEN MOCHE AND CHICAMA RIVERS, NORTH COAST OF PERU - Echevarría López, Gori Tumi (2015)
The article describes and analyzes a segment of the archaeological road that crosses the area between the Moche and Chicama rivers, going through the confluence of the Piedra Parada and Portachuelo hills, being the only known in the zone that uses the area of mountains as part of their way following a North - South general orientation. From the observations and findings the authors discuss the construction and road design characteristics, as well as the aspects of temporal correspondence and continuous use. It is stresses that this is only a section of the road, being one of the most important of the entire system.